History teaching based on the theory of Multiple Intelligences: The story of an action research case study - Duarte Nuno Duarte (Ricerche di Pedagogia e Didattica)
Within the framework of concerns about ensuring inclusion and equity of opportunities for school access and success, an action research was developed within the context of the professional practice of a teacher training course in Portugal. This (case) study consists of exploratory action research regarding the didactic-pedagogical mobilization of Gardner’s theory of Multiple Intelligences within the framework of history teaching in Portuguese secondary education. The research aimed to assess the relevance of a teaching-learning strategy based on Gardner’s theory in this localized study context. A mixed methodology was used for the data collection (questionnaire survey and documental analysis), with a tendentially qualitative data analysis. The sample consisted of 58 students from two school classes. The results suggest the relevance of the implemented approach, with gains for students in motivation, performance, and outcomes. It was also found that students perform more significantly when they act according to their intellectual predispositions.